Evaluation of hearing and speech-language in preschool children: how important, why we should perform? - Tokgöz-Yılmaz, Suna; Özcebe, Esra; Türkyılmaz, Meral Didem; Köse, Aysen; Sennaroğlu, Gonca; Orhon, Filiz; Ulukol, Betül (The Turkish Journal of Pediatrics, 2013)
The aim of the study was to present the hearing and speech-language findings of preschool children. The children in this study were aged 3-5 years. Sixtyseven of 239 children (28.0%) had been referred to a physician because of possible middle ear problems, and 25 of the 67 children had slight and mild conduction type hearing loss with air-bone gaps. One of 239 children had profound sensorineural hearing loss. Speech-language problems were found in 70 of 239 children (29.3%). Necessary attention should be paid to the evaluation of hearing and speech-language skills in preschool-aged children to avoid delayed detection and to give these children the opportunity for timely intervention for hearing and speech-language problems.